2014
DOI: 10.1161/circulationaha.114.006185
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac CaM Kinase II Genes δ and γ Contribute to Adverse Remodeling but Redundantly Inhibit Calcineurin-Induced Myocardial Hypertrophy

Abstract: Background Ca2+-dependent signaling through CaM Kinase II (CaMKII) and calcineurin was suggested to contribute to adverse cardiac remodeling. However, the relative importance of CaMKII versus calcineurin for adverse cardiac remodeling remained unclear. Methods and Results We generated double-knockout mice (DKO) lacking the 2 cardiac CaMKII genes δ and γ specifically in cardiomyocytes. We show that both CaMKII isoforms contribute redundantly to phosphorylation not only of phospholamban, ryanodine receptor 2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
167
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 156 publications
(182 citation statements)
references
References 47 publications
9
167
2
1
Order By: Relevance
“…19 Whereas after aortic banding and Iso stimulation, cardiac expression of Rcan1-4 as a measure for calcineurin activity was highly upregulated in CaMKIIδγ-knockout mice 19 ; this was not the case in DVL mice (data not shown). As cardiac hypertrophy in CaMKIIδγ-knockout mice after aortic banding and Iso stimulation was clearly dependent on the calcineurin overacitvation, 19 the lack of that in DVL mice could explain why these animals were protected from cardiac hypertrophy. However, it remains unclear by which pathways aortic banding and Iso treatment, but not dishevelled-transgenic, lead to an overactivation of calcineurin in CaMKIIδγ-knockout mice.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…19 Whereas after aortic banding and Iso stimulation, cardiac expression of Rcan1-4 as a measure for calcineurin activity was highly upregulated in CaMKIIδγ-knockout mice 19 ; this was not the case in DVL mice (data not shown). As cardiac hypertrophy in CaMKIIδγ-knockout mice after aortic banding and Iso stimulation was clearly dependent on the calcineurin overacitvation, 19 the lack of that in DVL mice could explain why these animals were protected from cardiac hypertrophy. However, it remains unclear by which pathways aortic banding and Iso treatment, but not dishevelled-transgenic, lead to an overactivation of calcineurin in CaMKIIδγ-knockout mice.…”
Section: Discussionmentioning
confidence: 88%
“…17,18 The phenotype of the CaMKIIδγ-knockout is described in detail in a separate article. 19 Interestingly, CaMKIIδγ-knockout reversed the phenotype caused by dishevelled-1 overexpression, whereas CaMKIIγ-knockout did not ( Figure S3), indicating that both the δ and γ isoforms of CaMKII are crucial in dishevelled-1-induced cardiac remodeling. To gain further insight into the mechanisms underlying these outcomes, we selected 4 mouse lines that were generated by crossing DVL mice with CaMKIIδγ-knockout mice: wild-type mice as control (CTRL), CaMKIIδγ-deficient, and dishevelled-1 wild-type mice as CKO, dishevelled-1-transgenic mice with normal level of CaMKIIδγ as DVL, and dishevelled-1-transgenic mice lacking CaMKIIδγ as DWC ( Figure 1B; Table S1).…”
Section: Resultsmentioning
confidence: 94%
“…This doubleknockout model also highlights the importance of CaMKII inhibition and CaMKII phosphorylation-dependent mechanisms under pathological conditions. 13 However, it remains unclear whether and how these CaMKII isoforms affect the TMEM16A Cl − channel and TMEM16A-associated arterial SMC functions.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of both CaMKII isoforms leads to calcineurindependent cardiac hypertrophy but protection against heart failure. 13 In general, the consequence of hypertension is involved in SMC hypertrophy, hyperplasia, migration, apoptosis, and contraction. The accumulating evidence has demonstrated that promotion of VSMC proliferation occurs in some certain forms of hypertension 15,22-25 whereby persistent elevation of Ang II level gives rise to vascular remodeling, indicating that VSMC proliferation may play a pivotal role in the progression of hypertensive vascular remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we examined calcineurin-NFAT activity and the fetal gene program. In Fgf13 KO mice subjected to TAC, we assessed calcineurin activity by measuring the expression of regulator of calcineurin 1 (Rcan1), a gene target of calcineurin (35). Fgf13 KO significantly attenuated the TAC-induced increase in Rcan1 expression observed in MCM mice (Fig.…”
Section: Fgf13 Ko Increases Sarcolemmal Caveolae Density In Cardiacmentioning
confidence: 97%